Short-term dynamic psychotherapy – indications and contraindications based on the case study “Lonely by choice” - Gryniuk-Toruń, Iwona; Tuszyńska-Bogucka, Wioleta (Current Problems of Psychiatry, 2013)
Recently, Short-Term Dynamic Psychotherapy (STDP) has been one of the most frequently chosen forms of therapy. “Insight”, that is becoming aware of secret motives, desires and mechanisms underlying patient’s problems, is regarded as the basic therapeutic factor, whereas the objective is accomplishment of deep and permanent changes in the structure of personality. This study is to show its possible uses in treatment of one of an increasingly widespread problems reported by young people, namely the so called loneliness by choice (“singlism”) as well as the need to identify indications and contraindications to the application of STDP in working with this age group.